Wilderness Medicine Curricula in United States EMS Fellowship, Emergency Medicine Residency, and Wilderness Medicine Programs. Issue 6 (10th December 2022) - Holstrom-Mercader, Maria; Kass, Daniel; Corsetti, Monica; Flamm, Avram
Abstract: Objective: Wilderness Medicine (WM) focuses on care delivered in austere or resource-scarce environments. The Accreditation Council for Graduate Medical Education (ACGME) requirements and core content for Emergency Medicine (EM) residency and Emergency Medical Services (EMS) fellowship in the United States (US) include some WM topics that are covered to varying degrees in these programs. Furthermore, there are no ACGME-approved WM fellowships or specific curricula. Different training programs may develop WM content and curricula that differ significantly, leading to variations in WM competencies and training. In 2009, the American College of Emergency Physicians (ACEP) Wilderness Medicine Section created a Fellowship Subcommittee and Taskforce to develop a standardized curriculum and core content for EM-based WM fellowships. However, to date, EMS fellowship and EM residency WM curricula in the US content have not been analyzed for consistency with the ACEP WM fellowship curriculum. Methods: In this study, the WM curricula components of EM residency and EMS fellowship were evaluated using the ACEP WM fellowship curriculum as a control. Potential curriculum gaps for each program type were identified. Results: Of the 19 WM competencies developed by the ACEP Wilderness Medicine Section Fellowship Subcommittee and Taskforce, EMS fellowship covers more WM topics (16 topics, or 84%) than EM residency (12 topics, or 63%), and combined, they cover 89% of these topics. Conclusions: By expanding to cover two additional WM topics, all WM curricula topics recommended by the ACEP WM fellowship curriculum could potentially be covered in EM residency + EMS fellowship; however, the depth of education in each topic may vary. It may be beneficial for Graduate Medical Education (GME)-level learners for programs to implement hands-on educational experiences in WM topics.